Isolation and Characterization of Cellulose Degrading Bacteria From Decomposing Empty Fruit Bunches (EFB) and Pineapple Wastes - Mazidatul Ashiqeen Balqiah, Mohamad Lazim (Universiti Malaysia Sarawak (UNIMAS), 2010)
Oil palm empty fruit bunches (EFB) and pineapple wastes are the most abundant cellulosic wastes in our country. In this research, a total of 14 strains of bacteria that are able to utilize carboxymethyl cellulose have been successfully isolated from decomposed oil palm empty fruit bunches and pineapple waste. Some of the isolates were also found to be resistance to heavy metals and antibiotics. Morphological characterization using gram staining and some biochemical test were carried out to determine the genera of the strains. Results showed that the strains belong to genera Azotobacter, Acetobacter, Bacillus, Cellulomonas, Micrococcus and Staphylococcus. To indicate the cellulolytic activities, hydrolysis zone on 0.5% carboxymethylcellulose (CMC) agar was measured. DNS assay was performed for quantifying the reducing sugar produced and P6 1 strain found as the best cellulose degrading bacteria. Plasmid DNA isolation attempted on the best five strains to detect presence of plasmid that may carry cellulose degrading gene. However, none of strains showed the presence of plasmid DNA.